KARAKTERISTIK SILIKA POWDER BERBASIS BATUAN TRAS DENGAN PROSES EKSTRAKSI DAN PRESIPITASI - Siswanto; Kurniati, Eli (Journal of Research and Technology, 2020)
Indonesia is a country rich in natural resources such as trass rocks where tras rock deposits in the Rembang area are 28.5 million m3 with a total area of ​​260 ha. Tras rock is only used for cement and brick raw materials where the economic value is low. Based on laboratory analysis, tras rock contained of SiO2 = 40-56%. Because of the high silica content, it was very possible to make a silica product that was widely used for industrial needs. The purpose of the research was to obtain optimum conditions in the extraction and precipitation process and also drying to obtain synthetic powder silica that met industry standards. The process carried out was refinement of 100 mesh size trass rock followed by an extraction process with variations in the concentration of NaOH (1; 1.5; 2; 2.5; 3M) and extraction time (60, 90,120, 150, and 180 minutes) in the reactor at a temperature 95°C then the solution was filtered and the precipitation process was carried out with 37% HCl through the neutral of pH, the resulting sludge was dried and the content and weight were calculated and the marfology was tested by SEM. The optimum conditions for of silica extraction proces of tras rock was the addition of 3M NaOH with a time of 150 minutes to produce 15.26 grams of silica.